Hypoglossal nerve monitoring, a potential application of intraoperative nerve monitoring in head and neck surgery (2013)
ABSTARCT: Intraoperative nerve monitoring (IONM) has many applications in different surgical fields. In head and neck surgery, IONM has been used to perform surgery of the parotid, thyroid and parathyroid glands, preserving the facial and recurrent nerves. However, hypoglossal nerve euromonitoring has not been addressed with such relevance.